Neutralizing antibodies and restriction factors cooperatively exert selective pressure on the HIV-1 envelope glycoprotein - Marceau, Thomas; Migraine, Julie; Moreau, Alain; Arrouche, Youness; Andriantsoanirina, Valérie; Verrier, Bernard; Mammano, Fabrizio; Meyer, Laurence; Braibant, Martine (AIDS (London), 2025)
Objective:This study investigates the evolving susceptibility of HIV-1 envelope glycoproteins (Env) to restriction factors (IFITM3, SERINC5, MARCH8) as the infection progresses from the early to chronic phase, and explores the interplay between these factors and the humoral immune response, particularly neutralizing antibodies (NAbs).Design:We compared Env variants isolated from five subjects during the early and chronic phases of HIV infection. The study focused on evaluating the sensitivity of these variants to three restriction factors and their susceptibility to neutralization by autologous antibodies and human monoclonal antibodies (HuMobNAbs).Methods:Env-pseudotyped viruses were generated by co-transfecting HEK293T cells with plasmids encoding Env variants and restriction factors. Viral infectivity was measured using TZM-bl cells. Additionally, neutralization assays were performed with autologous serum samples and HuMobNAbs to assess how early and chronic variants responded to neutralizing antibodies in the presence or absence of restriction factors.Results:Env variants from the early phase were more sensitive to the antiviral effects of IFITM3, SERINC5, and MARCH8 compared to those from the chronic phase. Incorporating IFITM3 and SERINC5 into viral particles also increased the sensitivity of variants to autologous neutralizing antibodies and HuMobNAbs.Conclusions:HIV-1 Env evolution leads to resistance to both innate immune restriction factors and adaptive immune responses over time. However, incorporating IFITM3 and SERINC5 into virions enhances their sensitivity to neutralizing antibodies, suggesting a potential cooperative effect that could be exploited in therapeutic strategies. Further research is needed to investigate the mechanisms behind this enhancement and its potential impact on treatment approaches.